How to re-found RRI in a cosmopolitan world? A case study of BGI, the frontier genetic enterprise in China - Han Zhang; Jie Gao; Feng Zhang (Journal of Responsible Innovation)
Re-founding RRI in a cosmopolitan world is a philosophical project aimed at global justice. Originating in Europe, RRI's introduction outside Europe sits in tension with nationalism. To explore strategies to re-found RRI in a cosmopolitan context in China, we analyzed a frontier genetic high-tech enterprise based in Shenzhen known as BGI. By exploring two crises BGI encountered over the past 25 years, which were regarded as turning points in building the enterprise RRI system, we conclude the following: (1) The rapid development of nationalism has undermined the cosmopolitan value of science and science ethics, even as science and technology were supposed to promote global cooperation; (2) To promote global justice, cosmopolitan RRI must consider intercultural value differences; (3) Humanizing RRI is a new approach to RRI practice that, instead of individual-centered responsibility, emphasizes reflective, collective responsibility, which fits with the character of scientific production in the era of big science.